Influence of Calcination Temperature on Size, Morphology and Optical Properties of ZNO/C Composite Synthesized by a Colloidal Method - Siham Lhimr; Saidati Bouhlassa; Bouchaib Ammary (Indonesian Journal of Chemistry, 2021)
ZnO is one of the most studied semiconductor materials because of its interesting chemicals, and from a technological point of view, mainly as a consequence of their outstanding properties, such as wurtzite type, non-toxic nature, large band gap, low cost, and environment-friendly. In this work, the ZnO/C composite was synthesized by a simple and fast low-temperature method; the solid product was calcination temperature at 100 to 400 °C. The influence of variation in calcination temperature was studied using X-ray diffraction (XRD), Fourier transforms infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and UV-visible diffuse reflectance spectroscopy. The X-ray diffraction patterns indicated a high crystallinity and a nanocrystalline size of the ZnO/C composite hexagonal structure of wurtzite. The SEM image of the samples showed that the powder has a spherical structure of flakes aggregated in the common nucleus like a grid. The sphere consists of spindle and flower-like structures. The optical properties were determined by UV-vis diffuse reflectance spectroscopy, and it was found that the band gap energy of ZnO/C composite increase from 3.210 to 3.329 eV with an increase in calcination temperature from 100 to 400 °C. FTIR spectra and EDS analysis showed that the existence of carbon in the composite.